Beam emission spectroscopy turbulence imaging system for the MAST spherical tokamak. - Field, A; Dunai, D; Gaffka, R; Ghim, Y; Kiss, I; Mészáros, B; Krizsanóczi, T; Shibaev, S; Zoletnik, S (2012)
A new beam emission spectroscopy turbulence imaging system has recently been installed onto the MAST spherical tokamak. The system utilises a high-throughput, direct coupled imaging optics, and a single large interference filter for collection of the Doppler shifted D(α) emission from the ~2 MW heating beam of ~70 keV injection energy. The collected light is imaged onto a 2D array detector with 8 × 4 avalanche photodiode sensors which is incorporated into a custom camera unit to perform simultaneous 14-bit digitization at 2 MHz of all 32 channels. The array is imaged at the beam to achieve a spatial resolution of ~2 cm in the radial (horizontal) and poloidal (vertical) directions, which is sufficient for detection of the ion-scale plasma turbulence. At the typical photon fluxes of ~10(11) s(-1) the achieved signal-to-noise ratio of ~300 at the 0.5 MHz analogue bandwidth is sufficient for detection of relative density fluctuations at the level of a few 0.1%. The system is to be utilised for the study of the characteristics of the broadband, ion-scale turbulence, in particular its interaction with flow shear, as well as coherent fluctuations due to various types of MHD activity.